2003
DOI: 10.1167/iovs.03-0591
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Signaling Pathways Associated with Corneal Epithelial Cell Apoptosis

Abstract: UV-irradiation-induced corneal epithelial cell apoptosis is mediated through activation of the SEK/JNK signaling pathway. Such activation is dependent on increases in K+ channel activity, which play an important role in the early events that result in activation of this pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 45 publications
8
73
0
Order By: Relevance
“…The inhibitory effect of these blockers on JNK signaling pathway is rather specific because there is a good correlation for the blockers to inhibit UV irradiationinduced JNK activation and Kv channel activity. The dose-response curve demonstrates that 4-AP effectively inhibits JNK activity with an IC 50 of ∼170 μM (Wang et al, 1999a;Lu et al, 2003). This IC 50 value is very close to the IC 50 value that is required for 4-AP to block the K + current in patch clamp studies.…”
Section: Uv-induced K + Channel and Jnk Activationsupporting
confidence: 54%
See 4 more Smart Citations
“…The inhibitory effect of these blockers on JNK signaling pathway is rather specific because there is a good correlation for the blockers to inhibit UV irradiationinduced JNK activation and Kv channel activity. The dose-response curve demonstrates that 4-AP effectively inhibits JNK activity with an IC 50 of ∼170 μM (Wang et al, 1999a;Lu et al, 2003). This IC 50 value is very close to the IC 50 value that is required for 4-AP to block the K + current in patch clamp studies.…”
Section: Uv-induced K + Channel and Jnk Activationsupporting
confidence: 54%
“…For example, we, as well as other researchers, have shown that stimulation of K + channel activity and dramatic loss of intracellular K + can result in apoptosis in the corneal epithelium, neurons, myeloblastic ML-1 cells, and other cell types (Schulz et al, 1996;Eldadah et al, 1997;Yu et al, 1997;Wang et al, 1999aWang et al, ,2003Lu et al, 2003;Trimarchi et al, 2002;Remillard and Yuan, 2004). It seems that there are dual functions of K + channels involving cell proliferation regulated by epidermal growth factor (EGF) (Lu et al, 2001a) and playing a role in mediating cell death induced by UV irradiation (Wang et al, 1999aLu et al, 2003). We found in corneal epithelial cells that K + channel activity is required for growth factor-stimulated activation of extracellularregulated kinase (ERK) (a MAP kinase) limb and proliferation.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations